"The world was shifting under our feet, so I turned to my devotionals as his dementia worsened": the role of spirituality as a coping mechanism for family caregivers of Alaska Native elders with dementia. Issue 3 (3rd July 2021) - Fife, Benjamin; Brooks-Cleator, Lauren; Lewis, Jordan P
ABSTRACT: Background : Providing direct care for an individual with Alzheimer's Disease and related dementias (ADRD) is a source of chronic stress for caregivers. Spirituality and religion are important to Alaska Native (AN) identity and this study explored the role of spiritual practices as a coping mechanism for dementia caregivers. Purpose : The aim of the study was to (1) identify stressors experienced by AN people caring for someone with dementia and (2) describe the role of spirituality in coping with those stressors. Methods : This exploratory study conducted interviews with 21 AN caregivers of those with dementia. We employed thematic analysis to interview transcripts to examine relationships among the narratives and explore themes that populated the participants' understandings of ADRD in each of the domains of Kleinman's Explanatory Model of Illness. Results : AN caregivers reported chronic stress related to caregiving, and subthemes included poor health, lack of support, and lack of education on dementia. Caregivers reported using spiritual practices to cope with stress. Conclusion : The use of spiritual practices is identified as a primary resource during challenging caregiving experiences. Community organizations and health care providers should incorporate spiritual practices as part of the support they provide to AN dementia caregivers.